COMPUTER-ASSISTED PROGRAMS OF ASSESSMENT AND STIMULATION OF VERBAL COMPREHENSION FOR STUDENTS WITH HEARING IMPAIRMENT - RALUCA PETRUTA (MARE); MARIA ANCA (Studia Universitatis Babes-Bolyai, 2010)
ABSTRACT. The study investigates the effects of adapted computer program on training the verbal comprehension at students with hearing impairment. Participants: 10 students with different degrees of hearing impairment were pre-tested for verbal comprehension with an adapted vocabulary scale. The following 10 sessions of computer-assisted training offered an alternative method of learning. Final results revealed that further stimulating and developing of verbal comprehension for students with hearing impairment can be achieved by diversifying the topics approached in schools through alternative methods and materials.